If you traveled West in a covered wagon - Levine, Ellen; Freem, Elroy (New York : Scholastic, 1986)
Tells you what it was like to be a pioneer and travel west to Oregon in the 1840s.
Keywords: Westward Expansion -- Non-Fiction